Comparative evaluation of soft tissue changes in Class I borderline patients treated with extraction and nonextraction modalities - Aniruddh Yashwant V.; Ravi K.; Edeinton Arumugam
Abstract Objective: To compare soft tissue changes in Class I borderline cases treated with extraction and nonextraction modalities. Methods: A parent sample of 150 patients with Class I dental and skeletal malocclusion (89 patients treated with premolar extraction and 61 patients without extraction) was randomly selected and subjected to discriminant analysis which identified the borderline sample of 44 patients (22 extraction and 22 nonextraction patients). Pretreatment and post-treatment cephalograms of the borderline subsample were analyzed using 22 soft tissue parameters. Results: Upper and lower lips were more retracted and thickness of the upper lip increased more in the borderline extraction cases (p < 0.01). The nasolabial angle became more obtuse and the interlabial gap was reduced in the borderline extraction cases (p < 0.01). Lower lip, interlabial gap and nasolabial angle showed no changes in the borderline nonextraction cases. Conclusion: The soft tissue parameters which can be used as guideline in decision making to choose either extraction or nonextraction in Class I borderline cases are upper and lower lip protrusion in relation to the E-plane and Sn-Pg' line, lower lip protrusion in relation to the true vertical line (TVL), upper lip thickness, nasolabial angle and interlabial gap.